English Teaching-Learning Process At The Fourth Year Of SDN Kiringan 1 Boyolali: An Ethnography - Endarini, Tri (2004)
This research aims to observe the English teaching-learning process at the forth year of SDN Kiringan 1 Boyolali. The research was conducted at SDN Kiringan 1 Boyolali in JL. Tentara Pelajar no.88. The problem of the study is how is the English teaching-learning process at the fourth year conducted, what is the result of English teaching learning process and what are the strengths and the weaknesses of English teaching-learning process at the fourth year of SDN Kiringan Boyolali. In this research the data are derived from event, informant and document. In collecting the data, the writer uses observation and interview. The writer uses descriptive qualitative in analyzing the data. Based on the data analysis, the objective of the teaching is to make the students are being already and confidence in learning English language furthermore and to introduce English as the first foreign language. The roles of the teachers are as a manager, as a facilitator, as a counselor, as an instructor. The roles of the learners are as the subject of and as negotiator. The type of syllabus is the topic-based syllabus. The teacher uses handbook entitled Start With English: The English Book for Elementary School" as the teaching material. The teacher uses ESA: Engage, Study, Activate as the classroom procedure. In conclusion, the English teaching-learning process at the fourth of SDN Kiringan 1 Boyolali is successful in achieving the goal of teaching. The teacher can motivate the students in learning English as the first foreign language. The students have high interest in following English teaching learning process.